Hippocampal function in healthy carriers of the CLU Alzheimer's disease risk variant - Erk, Susanne; Meyer-Lindenberg, Andreas; Boberfeld, Carola Opitz von; Esslinger, Christine; Schnell, Knut; Kirsch, Peter; Mattheisen, Manuel; Mühleisen, Thomas W.; Cichon, Sven; Witt, Stephanie H.; Rietschel, Marcella; Nöthen, Markus M.; et al. (The journal of neuroscience, 2011)
Alzheimer's disease is a devastating, common, progressive dementia with considerable heritability. Recently, a genetic variant associated with the disease was discovered at CLU (rs11136000) with genome-wide support. Here we show, using an imaging genetics approach in a large genotyped sample, that healthy carriers of the variant exhibit altered coupling between hippocampus and prefrontal cortex during memory processing, mirroring clinical evidence of disturbed connectivity in patients and providing a neurogenetic mechanism for CLU-associated risk and protection.